Erratum: NG, N. K. & MCLAUGHLI, P. A. (2009) A new hermit crab (Decapoda: Anomura: Paguroidea: Paguridae) from the eastern North Pacific. Zootaxa, 2227, 63–68. - Ng, N. K.; Mclaughli, P. A. (Zootaxa, 2009)
(Erratum)